Research on the Vehicle Routing Problem of Multi-Vehicle Types Electric Vehicles Considering Piecewise Linear Charging and Load Impact on Energy Consumption - Lv, Siqiang (International Journal of Computer Science and Information Technology, 2024)
With the introduction of policies such as green logistics and green supply chains, the application of electric vehicles in logistics distribution is becoming increasingly widespread. This paper starts from the vehicle routing problem of multi-vehicle types electric vehicles, introduces a non-linear charging strategy, and uses piecewise linear functions to fit the non-linear charging process. We propose a vehicle routing problem for multi-vehicle types electric vehicles considering piecewise linear charging and load impact on energy consumption, and construct a mixed integer programming model. An adaptive large-scale neighborhood search algorithm is designed to conduct experiments on small and large-scale instances to verify the performance of the model and algorithm.